2017
DOI: 10.1103/physrevlett.119.167401
|View full text |Cite
|
Sign up to set email alerts
|

Topologically Protected Complete Polarization Conversion

Abstract: We consider the process of conversion between linear polarizations as light is reflected from a photonic crystal slab. We observe that, over a wide range of frequencies, complete polarization conversion can be found at isolated wave vectors. Moreover, such an effect is topological: the complex reflection coefficients have a nonzero winding number in the wave vector space. We also show that bound states in continuum in this system have their wave vectors lying on the critical coupling curve that defines the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
83
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(86 citation statements)
references
References 33 publications
3
83
0
Order By: Relevance
“…The slab is placed on a mirror. In a recent paper, we showed that such a structure can achieve complete conversion between linear polarizations. And moreover such complete conversion is topological in nature, and hence can occur over a wide range of frequencies .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The slab is placed on a mirror. In a recent paper, we showed that such a structure can achieve complete conversion between linear polarizations. And moreover such complete conversion is topological in nature, and hence can occur over a wide range of frequencies .…”
Section: Introductionmentioning
confidence: 99%
“…In a recent paper, we showed that such a structure can achieve complete conversion between linear polarizations. And moreover such complete conversion is topological in nature, and hence can occur over a wide range of frequencies . Building upon our previous works, here we show that this structure can achieve arbitrary polarization conversion: For an incident light with any given polarization, arbitrary output polarization can be achieved over a wide range of frequencies, provided that we simply vary the direction of the incident light with respect to the structure, without any modification of the structure.…”
Section: Introductionmentioning
confidence: 99%
“…These are artificial materials composed of two or more different constituents which form a macroscopic crystalline structure. A few important examples are gyrotropic photonic crystals [31][32][33], Floquet topological insulators [39][40][41] and bianisotropic metamaterials [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56]. Instead, we focus on the microscopic domain and utilize the periodicity of the atomic lattice itself.…”
Section: Introductionmentioning
confidence: 99%
“…The topological field theory of light has surfaced in knotted solutions of Maxwell's equations [10,11], as well as the uncertainty relations for photons [12]. Along side this, there have been important recent developments to formulate topological properties for photons utilizing photonic crystals and metamaterials [13][14][15][16][17][18][19][20][21][22][23][24][25]. The pioneering work in topological photonic crystals has shown the existence of edge states robust to disorder.…”
Section: Introductionmentioning
confidence: 99%